Mechanical Percussion Devices: A Survey of Practice Patterns Among Healthcare Professionals - Scott W Cheatham; Russell T Baker; David G Behm; Kyle Stull; Morey J Kolber (North American Sports Medicine Institute, 2021)
# Background Mechanical percussion devices have become popular among sports medicine professionals. These devices provide a similar effect as manual percussion or tapotement used in therapeutic massage. To date, there are few published studies or evidence-based guidelines for these devices. There is a need to understand what professionals believe about this technology and how they use these devices in clinical practice. # Purpose To survey and document the knowledge, clinical application methods, and use of mechanical percussion devices among healthcare professionals in the United States. # Design Cross-sectional survey study. # Methods A 25 question online survey was emailed to members of the National Athletic Trainers Association, Academy of Orthopedic Physical Therapy, and American Academy of Sports Physical Therapy. # Results Four hundred twenty-five professionals completed the survey. Most professionals (92%, n=391) used devices from two manufacturers: Hyperice® and Theragun®. Seventy-seven percent directed clients to manufacturer and generic websites (n=329) to purchase devices. Most respondents used a medium and low device speed setting for pre- and post-exercise (62%, n=185), pain modulation (59%, n=253), and myofascial mobility (52%, n=222). A large proportion of respondents preferred a total treatment time between 30 seconds and three minutes (36-48%, n=153-204) or three to five minutes (18-22%, n=76-93). Most respondents (54-69%, n=229-293) believed that mechanical percussion increases local blood flow, modulates pain, enhances myofascial mobility, and reduces myofascial restrictions. Most respondents (72%, n=305) were influenced by other colleagues to use these devices. Sixty-six percent used patient reported outcomes (n=280) to document treatment efficacy. Live instruction was the most common mode of education (79%, n=334). # Conclusion These results are a starting point for future research and provide insight into how professionals use mechanical percussion devices. This survey also highlights the existing gap between research and practice. Future research should examine the efficacy of this technology and determine consensus-based guidelines. # Level of Evidence 3